Integrating Culturally Responsive Teaching in The Development of Digital Students’ Worksheet for EFL Writing - Ramadhani , Firda Putri; Khoiriyah; Faizin (Universitas Sulawesi Barat, 2026)
This study aims to develop interactive e-worksheets as a learning medium for narrative text material for grade XI students using the ADDIE model. Based on the analysis of teachers and students, it was found that students often have difficulty in understanding the structure and elements of narrative texts and lack interest in traditional learning. Therefore, e-worksheets were developed by utilizing digital technology through the Liveworksheets platform, which provides interactive activities to improve students' writing skills. This e-worksheet is designed with a Contextual Teaching and Learning (CTL) approach and an integration of culturally responsive teaching, which was adapted to the Indonesian cultural context, to make the material easier to comprehend for EFL students. At the implementation stage, the product was tested on students with an average score of 86.61 from student responses, 90.90 from material experts, and 90.38 from media experts, indicating that the product is feasible to use. Evaluation from teachers shows that the use of e-worksheets can improve students' writing skills and motivation in understanding narrative texts. Overall, this study confirms that the implementation of technology-based interactive e-worksheets can serve as an effective and innovative alternative to enhance the quality of narrative text learning in schools. Further, some pedagogical suggestions are also highlighted.